Live Donor Laparoscopic Nephrectomy. Experience in 75 Cases [Nefrectomía Laparoscópica de Donante Vivo: Experiencia de 75 Casos Consecutivos] - Alarcon-Alvarez, E (Sociedad de Cirujanos de Chile, 2015)
Background: Live donor laparoscopic nephrectomy. Experience in 75 cases Background: Live Donor Laparoscopic Nephrectomy (LDLN) has substantial benefits when compared with open nephrectomy such as shorter hospital stay, prompt return to work, less post-operative pain, better cosmetic results, less blood loss and less surgical wound infections. It is the mode of choice for safely harvesting a kidney for organ transplantation. Aim: To describe the surgical results of LDLN in a pioneer renal transplant center in Chile. Material and Methods: Review of clinical records of 75 subjects aged 27 to 60 years (37 males) subjected to a LDLN in a public hospital between 1998 and 2013. Information about clinical and surgical data and perioperative complications was retrieved. Results: No subject died. All kidneys were satisfactorily implanted in their receptors. The mean operative time was 116 minutes. Mean hospital stay was 1.6 days, warm ischemia time was 6.8 minutes, and cold ischemia time was 31.5 minutes. Operative adverse events occurred in 8%. The conversion and reoperation rates were 4 and 1.3%, respectively. Among receptors,1.5% evolved with Acute Tubular Necrosis and 2.2% required graft excision. Conclusions: LDLN is a safe and pioneering surgical technique in Chile. Its results are satisfactory and comparable to those obtained with classic lumbotomy. © 2015, Sociedad de Cirujanos de Chile. All rights reserved.